2019
DOI: 10.1007/s10517-019-04343-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibodies to Glutamate on Age-Related Memory Changes in C57Bl/6 Mice

Abstract: Chronic intranasal administration of antibodies to glutamate to aging C57Bl/6 mice improved passive avoidance conditioning, had no effect on horizontal and vertical locomotor activity, but slowed locomotion in the open-field test. Administration of antibodies to glutamate increased the content of dopamine and its metabolites in mouse hippocampus, but had no effect on the metabolism of neurotransmitter amino acids. In the frontal cortex, antibodies to glutamate did not affect neurotransmitter metabolism, but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
2
0
6
Order By: Relevance
“…The study was conducted on 12-month old male C57Bl/6 mice (n = 24) and weighing 32. Abs-Glu were obtained according to the previously described method involving immunization of male chinchilla rabbits (n = 5) with a BSA/glutamate conjugate [2]. The purified polyclonal monospecific Abs-Glu was used in experiments in a titer of 1:1024 ± 1:16.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted on 12-month old male C57Bl/6 mice (n = 24) and weighing 32. Abs-Glu were obtained according to the previously described method involving immunization of male chinchilla rabbits (n = 5) with a BSA/glutamate conjugate [2]. The purified polyclonal monospecific Abs-Glu was used in experiments in a titer of 1:1024 ± 1:16.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we demonstrated that chronic intranasal administration of glutamate antibodies (Abs-Glu) to 12-month old C57Bl/6 mice (250 μg/kg) led to an improvement in passive avoidance test performance. Moreover, intranasal Abs-Glu did not affect motor activity in the open field test, indicating a selective effect of Abs-Glu on memory formation [2]. Consequently, the aim of this study was to investigate the effects of Abs-Glu on learning and spatial memory in the Morris water maze in relation to hippocampal and prefrontal cortical concentrations of biogenic amines, their metabolites and amino acid neurotransmitters in aging C57Bl/6 mice.…”
Section: Introductionmentioning
confidence: 96%
“…Показано, что введение АТ-ГЛ совместно с фибриллярными или олигомерными формами белка S100A9 не приводило к нарушению памяти у стареющих животных [4,5]. Эффект улучшения выработки УРПИ также наблюдался у стареющих мышей C57Bl/6 после 14 дневного интраназального введения АТ-ГЛ в дозе 250 мкг/кг и сохранялся у них в течение 7 дней после отмены антител [6,7]. При этом в гиппокампе мозга мышей, получавших АТ-ГЛ, было отмечено снижение содержания дофамина и повышение концентрации его метаболитов, но не обнаружено их влияния на обмен нейромедиаторных аминокислот.…”
Section: Original Articleunclassified
“…При этом в гиппокампе мозга мышей, получавших АТ-ГЛ, было отмечено снижение содержания дофамина и повышение концентрации его метаболитов, но не обнаружено их влияния на обмен нейромедиаторных аминокислот. В префронтальной коре АТ-ГЛ не влияли на обмен нейромедиаторов, вызывая повышение уровня как возбуждающих, так и тормозных аминокислот, не изменяя их соотношения [6]. Через 7 дней после отмены АТ-ГЛ в гиппокампе мозга животных было выявлено повышение содержания дофамина и его метаболитов, а также повышение уровня аспарагиновой кислоты и таурина.…”
Section: Original Articleunclassified
See 1 more Smart Citation